2005
DOI: 10.1007/s10815-005-1499-z
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst Development After Cryopreservation and Subcutaneous Transplantation of Mouse Ovarian Tissue

Abstract: Purpose : To investigate follicle survival and developmental potential with IVF of cryopreserved, subcutaneously transplanted mouse ovarian tissue. Methods : Fresh and frozen mouse ovarian tissue was autologously transplanted into subcutaneous tissue. Two weeks after the transplantation, the morphology and histology of the fresh and frozen grafts were compared. Superovulation and IVF was performed to evaluate the fertility potential of the frozen ovarian graft. Results : Both fresh and frozen grafts of ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
9
0
2
Order By: Relevance
“…It has been hypothesized that poor folliculogenesis in cryopreserved ovaries is attributable to dysfunction of granulosa cells but not of oocytes [17,30]. Previously, we have shown that oocytes survive in adequate numbers in subcutaneously transplanted cryopreserved ovarian tissue [17]. Granulosa cells are reportedly more vulnerable to ischemia than primordial follicles [31], and in this study, we demonstrated a higher than normal rate of apoptosis in granulosa cells from cryopreserved ovaries (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…It has been hypothesized that poor folliculogenesis in cryopreserved ovaries is attributable to dysfunction of granulosa cells but not of oocytes [17,30]. Previously, we have shown that oocytes survive in adequate numbers in subcutaneously transplanted cryopreserved ovarian tissue [17]. Granulosa cells are reportedly more vulnerable to ischemia than primordial follicles [31], and in this study, we demonstrated a higher than normal rate of apoptosis in granulosa cells from cryopreserved ovaries (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Injury to granulosa cells may affect further folliculogenesis [19]. It has been hypothesized that poor folliculogenesis in cryopreserved ovaries is attributable to dysfunction of granulosa cells but not of oocytes [17,30]. Previously, we have shown that oocytes survive in adequate numbers in subcutaneously transplanted cryopreserved ovarian tissue [17].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations